THE IMAGES OF EGYPTIAN WOMEN IN 'CLEOPATRA WA MAC' SHORT STORY AND 'PUDARNYA PESONA CLEOPATRA' MINI NOVEL (CITRA PEREMPUAN MESIR DALAM CERPEN 'CLEOPATRA WA MAQ' DAN NOVEL MINI 'PUDARNYA PESONA CLEOPATRA') - Rahimal Khair (UIN Raden Mas Said Surakarta, 2020)
This study aimed to examine the images of Egyptian women in Cleopatra wa Maq short story written by Tawfiq al-Hakim and Pudarnya Pesona Cleopatra mini novel authored by Habiburrahman el-Shirazy. This research used a comparative literary approach and feminist literary criticism. The method used is descriptive analysis. The findings show that there are seven images of Egyptian women as follows: (1) women who are chosen because of their beauty, (2) women who are great and to be proud of but serve as the evidence of men's superiority, (3) women who are good at influencing men but not rational, (4) women who love luxurious and glamour lives under any circumstances, (5) women who are selfish and do not know about politics, (6) women who are easy to turn away, and (7) women who become the sources of sufferings or take responsible for men’s faults. Although the images of Egyptian women in both literary works have similarities, there are differences in each author’s creativity.